THE ROLE OF RENEWABLE ENERGY SOURCES IN FUTURE ENERGY CHALLENGES - I. M., DANMALLAM; H., NUHU (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
Currently, most of our energy supplies are based on fossil fuels, wherein the production and consumption of such finite energy sources when set side by side with the accessible reserves clearly reveal a serious future concern. Ever-increasing price of fossil fuels and global warming mediated climatic changes are associated with the intensive consumption of these fossil fuels for human comfort. In this view, the world cannot confidently rely on these finite fuel’s resources. Accordingly, making of a fuel with safer, efficient, cost-effective and convincingly green (ecological affable) characteristics is the key issue towards satisfying such demands. Attempt to address the opportunities provided by renewable energy generation technologies for meeting these future challenges of energy supply by exploring renewable energy technologies such as Solar, Wind, Biomass, Geothermal and Hydro as an alternative energy supply with a great future prospect. Amongst the renewable energy sources, solar and hydro energies have been extensively explored as sustainable alternative. However, photo voltaic technologies appear promising to replace the traditional fossil fuels as well. It has been acknowledged to provide huge amount of carbon footprint free energy to the growing population. Renewable energy sources especially solar, wind and hydroelectric are the preferred choices. Thus, advancement in these renewable energy technologies are necessary to tap the true potentials of the renewable energy resources. Making use of scaling-up approach and manifold policies, it is possible to accomplish environmentally responsible, reliable and affordable energies that would definitely make the Earth greener.